The Evaluation of the Museum’s Attractiveness for Cultural Tourism from the Visitors’ Perspective: Case Analysis of the BE “Neringos Muziejai” - Jonaitienė, Ernesta; Stasiunaitienė, Kristina (Jaunųjų mokslininkų darbai, 2021)
Cultural attractions, cultural sites and events are an important motive for travel. The participation of museums in cultural tourism is linked to their activities. Museums, adapted to the challenges of modern society: digitization, increasing the number of services for visitors, presenting and selling new educational programs, adapting to a diverse audience, have the potential to attract more visitors. The needs of the today’s user of cultural tourism are high, and museums seek to reveal cultural content in an interesting, engaging, unexpected way.The aim of the research is to evaluate the opinion of the visitors of the Budgetary Establishment (BE) “Neringos muziejai” about the attractiveness of the museum for cultural tourism. To achieve this goal, the criteria for assessing the attractiveness of the museum as an object of cultural tourism were identified. On the basis of these criteria,  the visitors’ opinions about the attractiveness of the BE ,,Neringos muziejai” for cultural tourism were evaluated.The results of the research confirmed that the visitors of the BE “Neringos muziejai” are educated, middle-aged and higher-income people, for whom it is important to spend leisure time in meaningful and interesting ways, gain knowledge and experience. In their opinion, the attractiveness of this museum for cultural tourism would be enhanced by the overall museum environment, updated exhibitions, competent staff, events in the museum, innovativeness in using modern innovations and technologies such as multimedia, virtual tours, 3D projections, smart guides.
Keywords: cultural tourism; museum; visitor; attractiveness; innovation